2023
DOI: 10.1002/cam4.6781
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in cancer patients: The impact of vaccination on outcomes early in the pandemic

Fareed Khawaja,
Georgios Angelidakis,
Adina Feldman
et al.

Abstract: BackgroundWith the rapid evolution of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic, the development of effective and safe vaccines was of utmost importance to protect vulnerable individuals, including cancer patients. Studies comparing the clinical outcomes of cancer patients with or without vaccination against coronavirus disease 2019 (COVID‐19) have not demonstrated clear benefit. We aimed to determine the protective effects of COVID‐19 vaccination by comparing vaccinated and unv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(151 reference statements)
0
0
0
Order By: Relevance
“…Our study showed a lower trend but not statistical significance in both the seroconversion rate and percent inhibition assay in patients receiving chemotherapy three months prior or during vaccination in term of neutralization assay for both wild type and Omicron variant, regardless of leukopenia, neutropenia, and lymphopenia. However, overall effects of systemic treatments in cancer and vaccination on COVID infection outcomes remain unclear and inconsistent [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a lower trend but not statistical significance in both the seroconversion rate and percent inhibition assay in patients receiving chemotherapy three months prior or during vaccination in term of neutralization assay for both wild type and Omicron variant, regardless of leukopenia, neutropenia, and lymphopenia. However, overall effects of systemic treatments in cancer and vaccination on COVID infection outcomes remain unclear and inconsistent [27,28].…”
Section: Discussionmentioning
confidence: 99%